The Relationship Between Diet and Body Mass Index with Events of Acne Vulgaris among Medical Students - Bunga, Yeheskiel Holoaino; Manuputty, Amanda Gracia; Asmin, Elpira; Lestaluhu, Santi Aprilian; Djuhastidar Tando, Yudhie (Faculty of Medicine, Universitas Airlangga, 2024)
Background: Acne vulgaris is a chronic inflammatory disease of the pilosebaceous unit characterized by clinical features such as comedones, papules, pustules, and nodules that affect social and psychological functions. Foods containing carbohydrates with a high glycemic index can trigger acne vulgaris. Consumption of fatty foods, chocolate, milk, nuts, and cheese can stimulate the recurrence of acne vulgaris. Objective: This study aims to determine the relationship between dietary habits and body mass index (BMI) and the incidence of acne vulgaris among students of the Faculty of Medicine of Pattimura University. Methods: This research is an observational analytic study with a cross-sectional design. Samples were selected using a proportional stratified random sampling technique with a simple random sampling approach, totaling 89 respondents. Respondents were required to fill out the SQ-FFQ questionnaire and undergo height and weight measurements. Result: Out of 89 respondents, 81% frequently (≥2×/day) consumed carbohydrates 82% often (1×/day) consumed proteins and 71% often (1×/day) consumed reduced-fat. Regarding the quantity of intake, 55% of respondents consumed high carbohydrates per day, 69% consumed high proteins per day, and 24% consumed high fat intake per day. The prevalence of acne vulgaris was 66%p-value <0.05. Conclusion: There is a significant relationship between dietary habits based on carbohydrate, protein, and fat intake and the incidence of acne vulgaris. However, there is no significant relationship between BMI and the incidence of acne vulgaris among medical students at Pattimura University.